Pengaruh Strategi Pembelajaran Kooperatif Tipe STAD Versus Ekspositori dan Gaya Kognitif terhadap Hasil Belajar Konsep Fisika Siswa Kelas X SMA - Prayekti -- (Jurnal Pendidikan dan Kebudayaan, 2014)
This research aims to examining: 1) The learning outcomes differences on theunderstanding and application of physics concept between groups of students who learned through STAD cooperative learning and expository learning; 2) The learning outcome differences on physics concept understanding and application among students with different cognitive styles; 3) The learning outcome influences of physics comprehension; 4) The interaction effect between learning and cognitive style on learning outcomes of physics. This research used a quasiexperimental research with factorial of non-equivalent control group design, which is implemented in four classes, determined by lottery, such as XMIA A class, XMIA B class, XMIA C class, XMIA D class at SMAN 58 Jakarta Timur with 144 students altogether. Two classes were as the experimental classes and two other class were as the control classes. Learning outcomes data were collected through pretes and pos tes and analyzed by using statistical MANCOVA test helped by SPSS 15. The result showed that: 1) STAD learning strategy demonstrate learning outcomes of comprehension and application of physics concept is better than expository learning strategies; 2) students who have field independent cognitive styles demonstrate learning outcomes of comprehension physics concepts is better than students who have a field dependent cognitive style; 3) there is an interaction between learning strategies and cognitive style on learning outcomes of comprehension physics concepts; and 4) there is no interaction between learning strategies and cognitive style on learning outcomes of physics concepts application. STAD learning strategy demonstrate learning outcomes of comprehension and application of physics concept is better than expository learning strategies.ABSTRAK Penelitian ini bertujuan untuk menguji: 1) perbedaan hasil belajar pemahaman dan aplikasi konsep fisika antara kelompok siswa yang dibelajarkan dengan pembelajaran kooperatif tipe STAD dan pembelajaran ekspositori; 2) perbedaan hasil belajar pemahaman dan aplikasi konsep fisika antara siswa yang memiliki gaya kognitif berbeda;3) pengaruh interaksi antara strategi pembelajaran tipe STAD versus ekspositori dan gaya kognitif terhadap hasil belajar pemahaman fisika;dan 4) pengaruh interaksi antara strategi pembelajaran dan gaya kognitif terhadap hasil belajarfisika.Metode yang digunakan quasi eksperimen dengan rancangan faktorial nonequivalent control group design, yang dilaksanakan pada empat kelas, ditentukan melalui undian yaitu kelas A dan B sebagai kelas control sedangkan kelas C dan D sebagai kelas eksperimen di SMA Negeri 58 Jakarta Timur berjumlah 144 orang. Data hasil belajar dikumpulkan dengan pretes dan postes, dianalisis dengan menggunakan uji statistik MANCOVA berbantuan program SPSS 15. Hasil penelitian: 1) strategi pembelajaran tipe STAD menunjukkan hasil belajar pemahaman dan aplikasi konsep fisika yang lebih baik daripada strategi pembelajaran ekspositori; 2) siswa yang memilikigaya kognitif field independent menunjukkan hasil belajar pemahaman dan aplikasi konsep fisika yang lebih baik daripada siswa yang memiliki gaya kognitif field dependent; 3) terdapat interaksi antara strategi pembelajaran dan gaya kognitif terhadap hasil belajar pemahaman konsep fisika; dan 4) tidak ada interaksi antara strategi pembelajaran dan gaya kognitif terhadap hasil belajar aplikasi konsep fisika. Strategi pembelajaran kooperatif tipe STAD menunjukkan hasil belajar pemahaman konsep fisika yang lebih baik daripada strategi pembelajaran ekspositori, dan Terdapat perbedaan yang signifikan terhadap hasil belajar pemahaman konsep fisika pada kedua kelompok gaya kognitif.